2019
DOI: 10.1093/mnras/stz1935
|View full text |Cite
|
Sign up to set email alerts
|

Formation and material supply of an active-region filament associated with newly emerging flux

Abstract: With the observations of S DO/AIA 304 Å and NVST Hα bands, we present the formation process of an active-region filament in active region NOAA 11903 during the period from 02:00 UT to 10:00 UT on November 25, 2013. A series of jets occurring in the vicinity of the south-western footpoint of the filament directly ejected cool and hot plasma to filament height and supplied material for the filament. Some newly emerging flux is found in the vicinity of the filament south-western footpoint during these jets. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 92 publications
(103 reference statements)
4
21
0
Order By: Relevance
“…The process of chromospheric fibrils merging into the filament is solid evidence that the mass of a filament can be uploaded from the chromosphere. Compared with Zou et al (2016) and Wang et al (2019) who reported that material was injected into the filament through magnetic cancellation in the photosphere, the material supplied in our work in some way is more similar to the levitation model: material emerges into the high atmosphere with the rising magnetic structure (Oliver et al 1999;Kubo & Shimizu 2007). In addition to the material supply, the magnetic flux in the chromosphere also supplies into the filament magnetic system.…”
Section: Summary and Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The process of chromospheric fibrils merging into the filament is solid evidence that the mass of a filament can be uploaded from the chromosphere. Compared with Zou et al (2016) and Wang et al (2019) who reported that material was injected into the filament through magnetic cancellation in the photosphere, the material supplied in our work in some way is more similar to the levitation model: material emerges into the high atmosphere with the rising magnetic structure (Oliver et al 1999;Kubo & Shimizu 2007). In addition to the material supply, the magnetic flux in the chromosphere also supplies into the filament magnetic system.…”
Section: Summary and Discussionsupporting
confidence: 51%
“…It was realized that the large filament mass must come from the chromosphere, because a quiet, static corona is an inadequate mass source (Pikel'Ner 1971;Saito & Tandberg-Hanssen 1973). The following three models have been proposed to explain how the material is transferred from the low atmosphere to the corona: the injection model (Chae et al 2001;Wang et al 2019), levitation model (Poland & Mariska 1986;Lites 2005), and evaporation-condensation model (Antiochos et al 2000;Kaneko & Yokoyama 2017). In the injection model, cool plasma in the low atmosphere is ejected into the filament by chromospheric magnetic reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [220] studied the formation and eruption of a large filament associated with a recurrent surge event; they confirmed that surge activities can efficiently supply enough mass for filament formation, and continuous mass with momentum supplied by surges can result in the instability and even the eruption of the newly formed filament. Other similar studies suggest that the material for filament formation could be supplied by both cool surges and hot coronal jets [221,222]. All the above studies showed that jet material was injected into filaments from one end of the filament channels.…”
Section: Relation To Other Phenomenamentioning
confidence: 81%
“…By analyzing the spectroheliograms in the Skylab plate collection, Spicer et al (1998) found that the Ne and Mg abundance ratio in filaments deviates from that of the corona but is similar to that of the chromosphere, indicating that the filament material might originate from the lower atmosphere, and then somehow is transported to the corona. Based on the observations and simulations, three models have been proposed: the injection model (An et al 1988;Wang 1999;Wang et al 2019), the levitation model (Lites 2005;Okamoto et al 2008;Zhao et al 2017), and the evaporation-condensation model (Antiochos et al 1999). In the injection model, cold chromospheric plasma is directly ejected into the corona by chromospheric magnetic reconnection.…”
Section: Introductionmentioning
confidence: 99%